Pengaruh sudut pandang pemotretan dalam fotografi olahraga lari terhadap minat beli di Kota Surabaya - Nugraha, Nugraha; Zahro, Siti; Herdiana, Wyna (Institut Seni Indonesia Yogyakarta, 2025)
This study analyzes the influence of shooting angles in running sports photography on the purchase intention of photo works in Surabaya. Visual aesthetics serve as the main focus, emphasizing elements such as shooting angles, composition, expression, moment, and point of interest. Running events today are not only seen as fitness activities but also as a form of self-expression often captured through photography—especially for sharing on social media. This creates a symbiotic relationship between runners and photographers: runners seek compelling documentation, while photographers offer photography services with commercial value. This study adopts a qualitative approach through visual analysis of photographic works. An experimental method was applied by capturing images from various shooting angles—including high angle, eye level, and low angle—to observe consumer responses to the photos. A total of 29 photo buyers at the Surabaya Medic Air Run 2024 were involved to find out their visual preferences. The findings show that the high angle shooting perspective is more favored than the others, as it effectively captures runners’ movement patterns, track layout, and reduces distractions from foreground and background elements. Additionally, appropriate composition, subject expression, and timing significantly enhance the visual appeal of the photos.